Analisis Kesiapan Perusahaan Dalam Menghadapi Era Revolusi Industri 4.0: (Studi Kasus Pada FIFGroup Denpasar) - Putri, Ni Kadek Sri Adnyani; Karyada, I Putu Fery; Putra, I Made Endra Lesmana (Hita Akuntansi dan Keuangan, 2024)
The presence of Industry 4.0 has an impact on improving the economy because industry plays an important role in all sectors of life throughout the world. Industry 4.0 to increase the competitiveness of the national industry through the use of the latest technology and innovation. This study aims to determine FIFGROUP Denpasar’s readiness to face industry 4.0. Data collection was carried out by conducting interviews with several informants who felt they had an understanding of FIFGROUP Denpasar’s readiness to face industry 4.0. The data analysis step is carried out by collecting data, analyzing data which can then be drawn conclusions. From the results of the analysis that has been carried out, it can be seen that FIFGROUP Denpasar is ready to face industry 4.0, which can be seen from the size of the assessment of each indicator used to carry out the assessment.